THE IMPLEMENTATION OF ENGLISH PRESENTATION ASSIGNMENT TO ENHANCE EFL LEARNERS’ MATERIALS UNDERSTANDING - Putri, Santi Amelia; Jabu, Baso; Aeni, Nur (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This qualitative descriptive study investigates how English presentation assignments enhance EFL learners' understanding of the material. The independent variable is the English presentation assignment, while material understanding is the dependent variable. The study population comprises all learners from the English Education Study Program at Universitas Negeri Makassar, totaling five classes, with 12 learners as subjects. Data were collected through classroom observations and interviews and analyzed using data reduction, data display, and conclusion-drawing techniques. Findings indicate that the implementation of English presentation assignments significantly enhances learners' understanding by requiring them to organize and present information clearly, fostering deeper comprehension.